Self-organized semiconductor nano-network on graphene. (9th March 2017) - Son, Dabin; Jin Kim, Sang; Lee, Seungmin; Bae, Sukang; Kim, Tae-Wook; Kang, Jae-Wook; Hyun Lee, Sang
Abstract: A network structure consisting of nanomaterials with a stable structural support and charge path on a large area is desirable for various electronic and optoelectronic devices. Generally, network structures have been fabricated via two main strategies: (1) assembly of pre-grown nanostructures onto a desired substrate and (2) direct growth of nanomaterials onto a desired substrate. In this study, we utilized the surface defects of graphene to form a nano-network of ZnO via atomic layer deposition (ALD). The surface of pure and structurally perfect graphene is chemically inert. However, various types of point and line defects, including vacancies/adatoms, grain boundaries, and ripples in graphene are generated by growth, chemical or physical treatments. The defective sites enhance the chemical reactivity with foreign atoms. ZnO nanoparticles formed by ALD were predominantly deposited at the line defects and agglomerated with increasing ALD cycles. Due to the formation of the ZnO nano-network, the photocurrent between two electrodes was clearly changed under UV irradiation as a result of the charge transport between ZnO and graphene. The line patterned ZnO/graphene (ZnO/G) nano-network devices exhibit sensitivities greater than ten times those of non-patterned structures. We also confirmed the superior operation of a fabricated flexible photodetector based on the line patterned ZnO/G nano-network.